EFFECT OF LIGHT INTENSITY ON DIFFERENT BETELVINE GERMPLASM UNDER TERAI REGION OF WEST BENGAL - NISON BHUTIA; PARTHA SARATHI MEDDA; P. CHOUDHURI; A. GHOSH; G. PANDIT (The Bioscan, 2015)
The present field trial was conducted in Himalayan Tract of West Bengal with three different light intensities (25%, 50% and 65%) and nine cultivars to standardize the optimum light requirement of different bangla cultivars and its effect on their growth, leaf yield and essential oil yield. The experiment was laid out in Split Plot Design. Lower light intensity (25%) recorded higher statistically significant linear growth during both active and dormant growth phase with increased leaf area(212.70 cm2), maximum vine elongation (26.15 cm), inter nodal distance(10.28 cm) and highest chlorophyll content (49.32). Cultivars like Simurali Gole Bhabna and Local recorded highest monthly yield (2.81no) under 25% light intensity over all cultivars. Interaction effect showed that for all the above characters the Bangla varieties under study gave maximum values in lowest light intensity. On the contrary due to more production of photosynthates higher light intensity gave significantly higher essential oil content (58.47 mg/100 g) of the leaves. Growing of betel vine under 25% light intensity may be considered optimum for better growth and higher leaf yield under closed type system of cultivation for all the cultivars under trial except Utkal Sudam and Bagerhat Local.